Developing A Nano-Fertilizer of Iron Oxide NPs Using Yeast Extract and Studying its Effectiveness on the Growth and Germination of Nigella sativa Seeds - Jihan Y. Al-Hatem; Duha A. Kadhim; Muslim A. Abid (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The use of nanofertilizers has increased dramatically in the last several years. Environmentally sustainable Fe2O3-nano-fertilizers are important for improving agricultural yields and physics. However, overuse of chemical nanofertilizers can have negative effects on both human health and the environment. Soil and plants are the most vital natural resources for human life and development, and both collect high concentrations of residues from nano-fertilizers. Numerous techniques have been proposed for producing nano fertilizers aimed at enhancing the germination rate, wetness, length, power, and dry weight of seedlings. A fresh study on the effects of hydrothermally prepared nano fertilizers made from yeast extract on the development and germination of Nigella sativa seeds. Fe2O3-Nano particles were produced with an average crystallite size of 12–39 nm, as shown by XRD. The FE-SEM-Pictures of Fe2O3-NPs display the morphologies of Nanostructures or Nano tapes. Fe2O3-NPs' optical properties reveal an absorbance band and an energy bandgap with maximal absorbance peaks at 231 nm and optical energy gaps of 3,8 eV, respectively. The outcome the impact of nano fertilizers (Fe2O3) on the development and germination of Nigella sativa seeds has been investigated through this activity. The study's treatments had a significant impact on the germination period; For example, when soaked in a suspension of baking yeast at a concentration of 1 g L-1, the germination period dropped to 14.71 days from 18.10 days for the control treatment. Less soaked in 1 mg L-1 of Nano Bread Yeast Extract, the Germination Duration was 14.16 days.